The Importance of Stoic Philosophy - Reilly, Leo (New Explorations, 2023)
The Stoic grammatical-rhetorical system of education was interrupted about 50 BCE by the intrusion of a rational logic (logica rationalis) which challenged the place of grammar. Marshall McLuhan and Albert Einstein are called as witnesses against the claims of this logic.